DEVOLUTION IN ITALIAN CULTURAL POLICIES MICRO VIEW AND ACTUAL IMPACTS - Monti, Stefano (Archeomatica, 2012)
Devolution has definitely become a ‘flagship' in the Italian political debate. It has affected any aspect of public policy over the last 17 years and the cultural sector has not been spared. Its key aim is to decentralise legal and administration powers in a way that could reduce the burden of State offices work and set up a more efficient and effective administration able to meet citizens' needs. After a long tradition of centralized policies and administration, long, costly and often in efficient procedures required a profound change. The reforms were so ledby the ideal to implement public policies closest to citizens' needs, to provide direct responses and increase their participation to local governments' actions (democratization and participative policy), to deliver more effective services (better performance) and distribute more equally the burden of administrative work of State offices (decentralisation of day-to-day administration). La Devolution e la politica culturale italiana La Devolution riveste un punto centrale nel dibattito politico italiano: ha riguardato ogni aspetto della politica pubblica negli ultimi 17 anni, e il settore culturale non ne è stato risparmiato. L'obbiettivo principale è quello di decentralizzare i poteri giuridici e amministrativi in modo da ridurre il peso del lavoro degli uffici pubblici statali, e di organizzare un'amministrazione più efficiente ed efficace in grado di soddisfare le necessità dei cittadini. Dopo una lunga tradizione basata su politica e amministrazione centralizzate, procedure lunghe, costose e spesso inefficienti richiedevano un profondo cambiamento. Le riforme sono state quindi indirizzate all'implemento di politiche pubbliche più vicine ai cittadini, a incrementare la loro partecipazione nelle azioni di governo locali (politica di democratizzazione e partecipativa), a fornire servizi più efficienti (migliori prestazioni) e a distribuire più equamente il carico amministrativo degli uffici statali (decentralizzazione dell'amministrazione quotidiana).